The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s12272-016-0738-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and controlled drug delivery system loading artersunate for effective chemotherapy on CD44 overexpressing cancer cells

Abstract: Poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles with negative surface charge were reversed to positive by cationic surfactant-DDAB before being coated with an anionic polymer, hyaluronic acid, to improve their site-specific intracellular delivery against CD44 receptor overexpressing cancer cells. Incorporating artesunate (ART)-a promising anticancer drug into PLGA/HA nanoparticles, is expected not only to overcome its poor aqueous solubility and stability but also enhance the activities. The obtained pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…It was observed suitable immunomodulation of the drug with high delayedtype hypersensitivity (DTH) response, increase of INF-c and IL-2 and reduction of IL-4 and IL-10 indicating Th1 immune response pattern resulting in clearance of the parasite [27]. Other studies conducted with PLGA NPs and other ART derivatives revealed high cytotoxicity in SCC-7, MCF-7 and HepG2 cell lines with growth inhibition and induced apoptosis, compared with free drugs [28,29].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 94%
“…It was observed suitable immunomodulation of the drug with high delayedtype hypersensitivity (DTH) response, increase of INF-c and IL-2 and reduction of IL-4 and IL-10 indicating Th1 immune response pattern resulting in clearance of the parasite [27]. Other studies conducted with PLGA NPs and other ART derivatives revealed high cytotoxicity in SCC-7, MCF-7 and HepG2 cell lines with growth inhibition and induced apoptosis, compared with free drugs [28,29].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 94%
“…The formulation was diluted by distilled water prior to three replicate measurements. After negative staining dispersion with 2 % (w/v) phosphotungstic acid, nanoparticles were placed into copper grid and observed by TEM (H7600, Hitachi, Tokyo, Japan) [24] .…”
Section: Physical Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Hyaluronic acid (HA) is a molecule with targeting specificity for the CD44 receptor. This linear glycosaminoglycan can bind to the surface of CD44-overexpressing cancers, which include cancers of the head and neck, as well as gastric, colon, prostate, hepatic and breast cancers [93,94]. However, the molecular weight of HA varies, which could affect cellular uptake [78]; thus, the efficacies of drug carriers might depend on the molecular weight of HA, which suggests that HA with an appropriate molecular weight will be selected for specific targets [95,96].…”
Section: Strategies For Targeting the Tumor Regionmentioning
confidence: 99%